Characterisation of three temperate phages released from the same Lactobacillus paracasei commercial strain - Capra, María Luján (2010)
Lysogeny entails more economical and technological risks in probiotic Lactobacillus casei/paracasei bacteria than in other lactic acid bacteria, due to economic value. Lysogeny is widely spread among Lactobacillus casei/paracasei strains. Siphophages CL1 and CL2, isolated from non-infected lysed-cultures of commercial L. paracasei A, are thermoresistant, have identical host spectrum, latent and burst times, whereas burst sizes are 148 and 85, respectively. Mitomycin C induction of L. paracasei A yielded prophage iA2, whose presence was confirmed on the strain genome and whose restriction patterns differed from phages CL1 and CL2. The latter shared several restriction fragments, probably indicating a common origin.